2007
DOI: 10.1080/07420520601142551
|View full text |Cite
|
Sign up to set email alerts
|

Rectal temperature, distal sweat rate, and forearm blood flow following mild exercise at two phases of the circadian cycle

Abstract: Changes in rectal temperature during mild exercise in the middle of the rising (11:00 h) and falling (23:00 h) phases of the circadian rhythm of resting core temperature have been compared. Seven healthy males were studied at rest, while exercising on a cycle ergometer (60 min at 80 W), and during the first 30 min of recovery. Rectal temperature, forearm blood flow, and forearm sweat rate were measured at 1 min intervals throughout. During exercise, there were significant time-of-day differences in the profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 42 publications
4
26
1
3
Order By: Relevance
“…Nonetheless, the underlying mechanisms of these time-of-day effects are still under discussion. Even if the circadian rhythm in core temperature is not necessarily the cause of the rhythm in muscle performance (Waterhouse et al, 2007), some studies have suggested that the simultaneous increases in central body temperature (assessed by oral or rectal measurements) and muscular power are causally related because the diurnal increase in central temperature may exert a beneficial passive warm-up effect (Bernard et al, 1998;Melhim, 1993;Racinais et al, 2005aRacinais et al, , 2005b. Although the exact mechanisms to explain this relationship are not known, it has been suggested that higher body temperature may enhance metabolic reactions, increase the extensibility of connective tissue, reduce muscle viscosity, and increase conduction velocity of action potentials (Shephard, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the underlying mechanisms of these time-of-day effects are still under discussion. Even if the circadian rhythm in core temperature is not necessarily the cause of the rhythm in muscle performance (Waterhouse et al, 2007), some studies have suggested that the simultaneous increases in central body temperature (assessed by oral or rectal measurements) and muscular power are causally related because the diurnal increase in central temperature may exert a beneficial passive warm-up effect (Bernard et al, 1998;Melhim, 1993;Racinais et al, 2005aRacinais et al, , 2005b. Although the exact mechanisms to explain this relationship are not known, it has been suggested that higher body temperature may enhance metabolic reactions, increase the extensibility of connective tissue, reduce muscle viscosity, and increase conduction velocity of action potentials (Shephard, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a peak of peripheral vasodilatation is observed in the late evening and a minimum in the morning, which respectively fit with the time of rapid decrease and increase of core temperature (Aschoff and Heise, 1972;Hildebrandt, 1974;Krauchi and Wirz-Justice, 1994;Smolander et al, 1993). These strategies are actually assimilated to ''heat gain'' mode in the morning and ''heat loss'' mode in the evening (Aldemir et al, 2000;Waterhouse et al, 2004Waterhouse et al, , 2007.…”
Section: Introductionmentioning
confidence: 87%
“…The thermal responses for a given exercise differ according to the time of day of the trial. Three studies have attempted to describe the effect of time of day on thermal response to exercise (Aldemir et al, 2000;Waterhouse et al, 2007;Morris et al, 2009). Aldemir et al (2000) proposed a 30 min cycling exercise designed to elicit 70% of individual VO 2max programmed at 08:00 h and 18:00 h. In this case, the diurnal temperature difference observed at the start of the exercise was no longer observed after 20 min of exercise.…”
Section: Introductionmentioning
confidence: 97%
“…In relation to thermoregulation, several studies have examined circadian rhythms in thermoregulation during exercise. Studies by Waterhouse et al 43,44) have shown that the thermoregulatory response during moderate-intensity aerobic exercise differs depending on the resting core temperature itself and the rising/falling phase of core temperature circadian rhythm. In these studies, the thermoregulatory response decreased at a lower core temperature and during the rising phase.…”
Section: A Variety Of Human Circadian Rhythms and Characteristicsmentioning
confidence: 99%
“…Better in the morning than in the evening Muscle strength 29,30) Sleep propensity 23) Body balance control 35) Accuracy 36) Maximal oxygen consumption 38) Aerobic contribution to Wingate test 40) Thermoregulatory responses 43,44) Primary factor to affect mental performance Psychomotor performance Physical performance and Fitness components…”
Section: Effects Of Exercise On Human Circadian Rhythmsmentioning
confidence: 99%